Prioritas konservasi lahan dan arahan programnya di Kelurahan Minas Jaya Provinsi Riau - Eno Suwarno; Hadinoto Hadinoto; Muhammad Ikhwan (Riau Journal of Empowerment, 2018)
Minas Jaya is one of the villages adjacent to Sultan Syarif Hasyim Forest Park (Tahura SSH). Tahura SSH is one of the conservation areas in Riau Province which is currently in critical condition due to forest encroachment, illegal logging, forest fires and illegal land conversion. In order to restore it requires an approach that combines conservation and community empowerment. One is the concept of Conservation Village. The initial stage in Conservation Village development needs to be a priority class map of conservation. The problems faced by partners to produce such maps require special expertise in spatial planning, mapping, and understanding of conservation village concepts. Based on the mapping identification showing that data of the conservation priority area 1, were identified it consisted of 243.92 hectares, then the conservation priority area 2 consisted of 257.87 hectares. Further, the conservation priority area 3 also identified and consisted of 504.28 hectares, moreover the conservation level 4 conservation area around 1,868.57 hectares, and conservation priorities 5 identified around 1,082.79 hectares. Conservation program directives were linked to each priority of conservation classes. It generally includes a good forest covers protection activities, enrich the land with tree crops. Furthermore, critical land rehabilitation with agroforestry patterns has the choice of species and proportion of annual crops and trees adapted to the degree of land criticality and gradient.